2021
DOI: 10.3390/nu13103402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Carrageenan in Inflammatory Bowel Diseases and Allergic Reactions: Where Do We Stand?

Abstract: Carrageenan (CGN) is a high molecular weight polysaccharide extracted from red seaweeds, composed of D-galactose residues linked in β-1,4 and α-1,3 galactose-galactose bond, widely used as a food additive in processed foods for its properties as a thickener, gelling agent, emulsifier, and stabilizer. In recent years, with the spread of the Western diet (WD), its consumption has increased. Nonetheless, there is a debate on its safety. CGN is extensively used as an inflammatory and adjuvant agent in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 60 publications
0
19
0
5
Order By: Relevance
“… 31 , 84 In addition, it has been proposed that carrageenan, a high molecular weight polysaccharide derived from red seaweed and which contains the galactose-alpha-1,3-galactose (alpha-gal) epitope, may also cause IgE-mediated symptoms of hypersensitivity in a minority of patients with AGS. 85 Carrageenan is used in several food products, including dairy products, frozen desserts, canned and cured meats, emulsified sauces, jelly candies, and some powdered products. 85 While there are case reports of IgE-mediated allergic reactions to carrageenan, 85 , 86 to date, there have been no reports demonstrating that such patients are also sensitized to alpha-gal.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 , 84 In addition, it has been proposed that carrageenan, a high molecular weight polysaccharide derived from red seaweed and which contains the galactose-alpha-1,3-galactose (alpha-gal) epitope, may also cause IgE-mediated symptoms of hypersensitivity in a minority of patients with AGS. 85 Carrageenan is used in several food products, including dairy products, frozen desserts, canned and cured meats, emulsified sauces, jelly candies, and some powdered products. 85 While there are case reports of IgE-mediated allergic reactions to carrageenan, 85 , 86 to date, there have been no reports demonstrating that such patients are also sensitized to alpha-gal.…”
Section: Managementmentioning
confidence: 99%
“… 85 Carrageenan is used in several food products, including dairy products, frozen desserts, canned and cured meats, emulsified sauces, jelly candies, and some powdered products. 85 While there are case reports of IgE-mediated allergic reactions to carrageenan, 85 , 86 to date, there have been no reports demonstrating that such patients are also sensitized to alpha-gal. There are also no reported cases of patients with alpha-gal syndrome experiencing severe allergic responses or anaphylaxis to carrageenan.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…λ-Carrageenan is widely used as a thickener, emulsifier, and stabilizer, but it was reported to stimulate the innate immunity, gut microbiota composition, and thickness of mucus barrier. On the other hand, the effect of λ-carrageenan on gut microbiota and inflammation is unknown [ 65 ]. The present study showed that λ-carrageenan intake, regardless of the MW, improved memory function and gut microbiota to reduce secondary bile acid biosynthesis degradation of toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the intake of fruits, vegetables, nuts, whole grains, fish and poultry is low. Emulsifiers, important additives to better palatability in processed foods, such as maltodextrin (MDX), carboxymethyl cellulose (CMC) (E466/E469), carrageenans (E407), as well as other food additives have been associated with intestinal microbiome alteration and inflammation (44,45).…”
Section: Dietmentioning
confidence: 99%